Effect Of Channel Length Variation On Analog And RF Performance Of Junctionless Double Gate Vertical Mosfet - Salehuddin, Fauziyah; Roslan, Ameer Farhan; Kaharudin, Khairil Ezwan; Mohd Zain, Anis Suhaila (Taylor’s University, 2019)
This paper investigates the effect of channel length (Lch) variation upon analogue and radio frequency (RF) performance of Junctionless Double Gate Vertical MOSFET (JLDGVM). The study has been performed under the fixed level of process parameters by considering the dependence of analogue and RF properties on the channel length. Furthermore, this paper aims to give a comprehensive insight on possible improvement in the performance of analogue and RF of the JLDGVM device. The structure and characteristics of the device are developed and extracted respectively via 2D TCAD simulation. The results show that both transconductance generation factor (TGF) and transconductance (gm) of the JLDGVM device are tremendously increased by 83% and 74% respectively as the scale of channel length is reduced from 12 nm to 9 nm. On the other hand, the unity gain cut-off frequency (fT) and the gain-band-width product (GBW) tremendously improved by ~93% and ~74% respectively as the channel length of the device is scaled from 12 nm to 9 nm.